Motivation for Creating the Baris Nadewa Creation Dance in the New Normal Era - I Gede Gunadi Putra; I Gede Mawan; I Bagus Wijna Bratanatyam (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
Baris Nadewa creation dance is one of the male dance creations whose existence is still relatively new in Bali. The duration of this dance is approximately 10 minutes and in each performance, this dance is accompanied by the Gong Kebyar gamelan instrument. Baris Nadewa dance is a duet dance because it is performed by two male dancers and each carries the property of a spear that looks like a bow. This dance represents the bravery and patriotism of Nakula and Sahadewa fighting on the battlefield. The creation of this dance was inspired by the characters Nakula and Sahadewa who are part of the Five Pandavas in the Mahabharata story. The idea of the movement comes from the development of the bebarisan dance movement (a traditional dance genre in Bali) that already existed before. The form of presentation of this dance represents the spirit of patriotism, courage, and skill of Nakula and Sahadewa in martial arts while on the battlefield. The motivation for creating this dance is none other than responding to the existence of radicalism that has begun to poison the younger generation in particular which  can break up national unity. Presented through dynamic and firm movements, indirectly the creation of this dance work wants to convey the message of the importance of cultivating patriotism, such as being brave, never giving up, and being willing to sacrifice for the nation and state. This study uses a qualitative descriptive research method to determine the function and motivation for the creation of the Baris Nadewa dance.